WTO domestic regulation and services trade : putting principles into practice / edited by Aik Hoe Lim and Bart de Meester. - Lim, Aik Hoe; De Meester, Bart (Cambridge University Press, 2014)
Domestic regulation of services sectors has a significant impact on services trade liberalization, which is why General Agreement on Trade in Services (GATS) disciplines are negotiated in the WTO. With the help of analyses and case-studies from academics, regulators and trade experts, this book explores the scope and limits of WTO legal principles to promote domestic regulatory reform. Case-studies discuss country-specific challenges and experiences of regulating important service sectors, such as finance, telecommunications, distribution, legal, education, health, postal and logistics services, as well as the role of regulatory impact assessments. The findings will interest trade officials, policy-makers, regulators, think tanks and businesses concerned with the implications of domestic regulation on access to services markets, and with the opportunities for formulating trade disciplines in this area. It is also a useful resource for academics and students researching regulatory approaches and practices in services sectors.